2021
DOI: 10.52711/0974-360x.2021.00471
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Acute complications and Quality of Life in Hemodialysis patients with Chronic Kidney Disease

Abstract: Introduction: End Stage Renal Disease (ESRD) is the last stage of Chronic Kidney Disease (CKD), where kidneys solely functions at 10 to 15 percent of their normal capacity. Efficacious treatment for ESRD is renal replacement therapies like dialysis and renal transplantation. Health related quality of life (HRQoL) is a neglected aspect of CKD care. Objective: To assess the acute complications and quality of life in hemodialysis patients. Methods: This prospective observational study was conducted for 6 months, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“… 44 However, some studies have not found any association between marital status with anxiety, depression, or QOL. 26 , 43 , 44 , 47 , 48 …”
Section: Discussionmentioning
confidence: 99%
“… 44 However, some studies have not found any association between marital status with anxiety, depression, or QOL. 26 , 43 , 44 , 47 , 48 …”
Section: Discussionmentioning
confidence: 99%
“…1,2,3 This rise has been paralleled by an increase in metabolic syndrome, a condition that heightens the risk of mortality from chronic kidney disease (CKD), as reported by LaGuardia HA et al 4 CKD, characterized by a gradual and progressive loss of renal function over at least three months, is a primary cause of end-stage renal disease (ESRD). 5 The global prevalence of CKD ranges from 8-16%, varying across different regions. 6 CKD is categorized into ve stages based on the degree of kidney damage or the estimated glomerular ltration rate (eGFR).…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Regrettably, the majority of patients remain unaware of their condition until it has advanced to a later stage. 9 Early cardiovascular disease (CVD), anemia, metabolic acidosis, and bone diseases are among the major complications associated with impaired kidney function. 10 The leading risk factors and predictors for CKD include impaired fasting plasma glucose, hypertension, and a high body mass index (BMI).…”
Section: Introductionmentioning
confidence: 99%